EXTERNAL AUDIT(OR) QUALITY AND ACCRUAL EARNINGS MANAGEMENT: FURTHER EVIDENCE FROM NIGERIA (Malaysian Management Journal, 2020)
Hinged on the quest for quality financial information, this study examined the influence of audit quality on restricting the incidence of accrual-based earnings management among 30 quoted non-financial firms in Nigeria, an emerging country which provides a rich institutional background and cultural setting different from developed nations. Secondary data were gathered from annual reports and audited financial statements for 11 years from 2008-2018. These firms were selected using stratified sampling technique. Thereafter, panel ordinary least square technique was used to estimate specified model for the study. While the descriptive statistics revealed the absence of accrualbased manipulation of earnings among quoted non-financial firms in Nigeria, the multivariate fixed effects ordinary least square depicted that audit quality variables adopted are mutually and statistically significant in explaining 49 percent changes in earnings management. Further, audit tenure and auditor independence exhibited positive and significant relationship, while total assets as the control variable, displayed a negative and significant influence on earnings management. Surprisingly, the size of audit firm appeared positive but statistically insignificant. Consequently, the relevant authorities and policy makers should not only sustain but improve on the current practice of audit engagement partner and/or auditor switch after certain years of continuous engagement to enhance their independence and reduce client-auditor engagement periods to avoid familiarity threat.JEL Classification Codes: M41, M42.